Numerical study of frequency effect on induction heating process in three dimensional - Abdol Jabbar Shokri (Progress in Physics of Applied Materials)
In this article, we investigate the effect of frequency as one of the important factors in the three-dimensional process of induction heating through numerical modelling. Induction heating is the process of heating electrically conductive materials by electromagnetic induction, which induces an eddy current within the material. Using the finite element method (FEM) and the comsol multiphysics software, we calculate the eddy current and the distribution of heat generated in both the workpiece and the inductor for different frequencies within the range of 0.75-5 kHz. To accomplish this, we utilize a real coil with a helix shape and a cylindrical workpiece. The results demonstrate that as the frequency increases, both the eddy current and the generated heat are transferred to the outer surface of the workpiece, becoming concentrated in a thin layer. In other words, these parameters exponentially decrease along the radius of the workpiece from the surface towards its interior.